1989
DOI: 10.1159/000163518
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adhesion of Metastatic Rat Mammary Carcinoma Cells to Organ-Derived Microvessel Endothelial Cells and Subendothelial Matrix

Abstract: The in vitro adhesion rates of rat 13762NF mammary adenocarcinoma cell clones of different spontaneous metastatic potentials to cloned microvessel endothelial cell monolayers and their subendothelial extracellular matrix were investigated. In this system, high rates of adhesion of the cloned tumor cell lines to syngeneic target (lung) organ-derived subendothelial matrix correlated with spontaneous metastatic potential, whereas adhesion to the lung microvessel endothelial cell apical surfaces occurred at lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The ability to respond to an organ-derived growth factor, however, would only be one of several important properties required for metastasis formation in that organ. For example, lung-metastasizing cells may also require adhesion to lung microvessel endothelial cells [6,7,17,38 J and subendothelial matrix [6,7,38 J.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to respond to an organ-derived growth factor, however, would only be one of several important properties required for metastasis formation in that organ. For example, lung-metastasizing cells may also require adhesion to lung microvessel endothelial cells [6,7,17,38 J and subendothelial matrix [6,7,38 J.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking result of the experiments shown in Figure 2 was the very low affinity of F9 cells for the ECM of the lungs. Specific binding to the subendothelial matrix may also be involved in determining the organ specificity of metastasis (Lichtner et al, 1989), and the clonal growth of tumor cells on tissue-specific biomatrices correlates with specific organ colonization (Doerr et al, 1989). This, however, does not seem to be the case for F9 cells since, after low-density plating, they grow at the same rate on both lung-and liver-derived ECM (not shown).…”
Section: The Role Of Cell Adhesionmentioning
confidence: 99%
“…46 Previous studies have demonstrated a correlation between the organ preference of metastasis and the in vitro adhesion rates of malignant cells to various endothelial cells 47,48 or subendothelial ECM. 49 Using colon carcinoma cell lines with different metastatic properties, we have shown that metastatic behavior correlates with different integrin-mediated adhesive properties. 50,51 However, differences in integrin expression could not explain these differences.…”
Section: Integrin Systemmentioning
confidence: 99%